Interchangeability between pneumococcal conjugate vaccines for pediatric use: a systematic literature review. (1st November 2020) - Nieto Guevara, Javier; Borys, Dorota; DeAntonio, Rodrigo; Guzman-Holst, Adriana; Hoet, Bernard
ABSTRACT: Introduction : Evidence on the interchangeability between the two pediatric pneumococcal conjugate vaccines (PCVs) – pneumococcal non-typeable Haemophilus influenzae protein D-conjugate vaccine (PHiD-CV) and 13-valent PCV (PCV13) – is limited but growing. We performed a systematic literature review to summarize evidence for PHiD-CV/PCV13 interchangeability regarding immunogenicity, safety, and effectiveness against pneumococcal disease. Areas covered : Seven records disclosing results from six studies on PHiD-CV/PCV13 interchangeability were identified. Four clinical trials showed that mixed schedules with a PHiD-CV-to-PCV13 switch at boosting or a PCV13-to-PHiD-CV switch during priming or at boosting were immunogenic with no apparent safety concerns. Two observational studies in the context of a programmatic PHiD-CV-to-PCV13 switch showed similarly high effectiveness against overall invasive pneumococcal disease with a mixed PHiD-CV/PCV13 schedule and a PCV13-only schedule. No effectiveness data for a PCV13-to-PHiD-CV switch and no immunogenicity/safety/effectiveness data for a PHiD-CV-to-PCV13 switch during priming were found. Expert opinion : For epidemiological or programmatic reasons, several local/national authorities have switched PCVs in their immunization programs. Consequently, children have received mixed schedules. Although herd immunity may obscure the individual effect, the limited data are reassuring. Additional evidence from these settings – especially effectiveness or impact data – may provide the necessary information for authorities to make informed decisions on interchanging PCVs. Abstract :